Usporedba učestalosti samoispravljanja između materinskoga i stranoga jezika - Kovač, Mirjana Matea (Slavistična revija, 2018)
This paper analyses a comparison of the frequency of appropriacy repairs and different information repairs in a the first (L1) and foreign language (L2) in order to gain new insights into the nature of the speech production monitoring system, as well as into the use of communication strategies. The classification of self-repairs is based on Levelt's model of speech production, the best empirically based speech processing model. The speech sample included 101 participants who performed five different speech tasks. The results indicate that in L1 the speakers use significantly more appropriacy repairs, which can be explained by the greater sensitivity of the monitor towards inappropriate speech. Due to the automated nature of L1 processing, speakers have more time and resources available to monitor speech. Furthermore, different information repairs belong to the category of speech disfluencies; however, they can also be considered communication strategies that speakers employ under time constraints in order to plan and form an utterance. L1 speakers use this category of self-repair significantly more frequently, suggesting that in a foreign language speakers do not show a tendency to use this strategy. They rather tend to solve difficulties in speech formation by using other strategies, such as grammatical reduction or filled pauses.
Keywords: govor; materni jezik; tuji jezik; večjezičnost